KONTRIBUSI PAJAK HOTEL DAN RESTORAN TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH KOTA SURABAYA - Karamullah, Fernanda Ayu; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research to find out the growth of tax revenue of hotel and restaurant in 2012-2014 periods, inorder to find out the amount of tax contribution of hotel and restaurantalso the efforts which has been carried outby the Local Government to increase the tax revenue of hotel and restaurant.The research method by usingqualitative approach. The collection data has been done by using documentation and interview. The data analysishas been carried out by using contribution analysis and analysis of effectiveness level. The result of this researchthe growth of hotel and restaurant tax during 2012-2014of 13.18% and 12.35%. Hotel and restaurant tax is notmaximal in giving their contribution to the Local-Own Sources (PAD). It can be seen from the percentage ofdistribution the hotel and restaurant tax to the Local-Own Sources (PAD) is only 5.49% and 7.50%.Meanwhile, The average of effectiveness level for the hotel and restaurant tax is 106,44% and 105,27%. Theseproven that, the effectiveness level is already maximal. Also the efforts which has been carried out by the Localgovernment in order to increase the tax revenue of hotel and restaurant which is conducting socialization to thetax payers and conductingperiodic data collection.Keywords: Hotel and Restaurant Tax, Contribution, Local-Own Sources.